Does physical therapy prevent post-operative delay in return of function following tension-band plating?. (December 2015) - Fillingham, Yale A.; Luthringer, Tyler; Erickson, Brandon J.; Kogan, Monica
Purpose: The clinical outcomes and complications of tension-band plating have been well documented, and commonly include a post-operative delay in return of function. We performed a retrospective comparison study to evaluate the capacity of immediate post-operative physical therapy to prevent this post-operative delay in return of function. Methods: Sixty-seven consecutive growth-deformity patients who were treated with tension-band plating at a single institution fulfilled the study criteria. Patients were allocated into two treatment groups: no post-operative physical therapy and immediately post-operative physical therapy. All patients were evaluated for delayed return of function, which was defined as use of crutches, lack of >90° flexion and full extension of the knee, or persistent pain requiring medication at the initial 2-week follow-up visit. Rates of delayed function were compared between the two treatment groups. Results: Among the study participants, 48 patients had no physical therapy and 19 patients had immediate post-operative physical therapy. Eighteen patients in the no physical therapy group reported a delay (37.5 %) while only 2 patients in the physical therapy treatment group reported a delay (10.5 %); p = 0.0386. Conclusions: Delayed return of function dramatically affects pediatric patients, causing unnecessary absence from school and strain on the caregiver. Therefore, it is important to identify treatment modalities to help mitigate the complications of surgery. We conclude that the use of immediate post-operative physical therapy statistically significantly helps patients to return more rapidly to their functional level.